Juvenile crime and justice - Chambliss, William J. (SAGE, 2011)
Presents arguments both in favor of and opposed to various treatments, programs, and punishments, examining issues such as youth curfews, juveniles in adult courts, legal representation for juveniles, juvenile boot camps, group homes, and out-of-home placement.
Keywords: Juvenile delinquency.; Crime.; Law enforcement.; Corrections.; Criminal justice, Administration of.; Délinquance juvénile.; Lois -- Application.; Services correctionnels.; SOCIAL SCIENCE -- Criminology.; Corrections; Crime; Criminal justice, Administration of; Juvenile delinquency; Law enforcement; Ungdomsbrottslighet -- Förenta staterna.; Reference works; Reference works.; Ouvrages de référence.